Application of choice experiment in assessing willingness to pay of tourist for marine conservation area in Tun Sakaran Marine, Malaysia Park - Latiff, Norasilah; Mohammad Afandi, Syamsul Herman; Shuib, Ahmad; Samdin, Zaiton (IDOSI Publications, 2015)
Tun Sakaran Marine Park (TSMP) is one of an ecotourism areas that has been gazetted as Marine Protected Area (MPA). At the same time TSMP is the resource for a variety of recreational activities such as snorkelling, sightseeing, diving and nature walk. TSMP is gaining popularity as suggested by increasing trend of tourist arrivals from 2007 to 2014. Despite the positive economic benefits tourism brings to TSMP, there is threat of degradation of marine resources if the resources are overuse. Nevertheless, there is no clear boundary between sustainable use and overuse of TSMP. This triggers the need to understand the value of conservation under actual condition and comparatively under hypothetical scenarios in regards to tourism activities in TSMP. The objective of this study is to assess the benefit that tourist obtained from marine ecosystem of TSMP by assessing their Willingness To Pay (WTP). To assess the hypothetical scenario of environmental setting of TSMP, this study adopts Choice Experiment (CE) as the method. Choice sets of attributes are established for respondents to choice. Data for the study was obtained via face to face interviews of tourists in Semporna. The values of willingness to pay (WTP) of conservation to the marine ecosystem is then solicited using the CE approach. The analysis of data shows that majority of respondents are willing to pay for marine conservation in rate RM 20 to RM40.